Association Between Nursing Management Functions and Nurses' Compliance with Fall Risk Prevention at Islamic Hospital Banjarmasin - Okta Nisa; Herman Ariadi; Diah Retno Wulan; Rohni Taufika Sari (Fakultas Kedokteran, Universitas Papua, 2026)
Falls are among the most common patient safety incidents in hospitals and may result in physical injuries, psychological trauma, and increased healthcare costs. Effective fall risk prevention requires a high level of nurses' compliance, which is influenced by nursing management functions, particularly the directing and controlling functions. This study aimed to examine the association between nursing management functions and nurses' compliance with fall risk prevention at Islamic Hospital Banjarmasin. This quantitative study employed a cross-sectional design. A total of 148 nurses were recruited using the total sampling technique. Data were collected using a Google Forms–based questionnaire and analyzed using Spearman's rank correlation test. The results showed that most respondents reported a high level of nursing management functions (60.1%) and high compliance with fall risk prevention (77.7%). Bivariate analysis revealed a significant association between nursing management functions and nurses' compliance with fall risk prevention (r = −0.730; p < 0.001). In conclusion, nursing management functions were significantly associated with nurses' compliance with fall risk prevention at Islamic Hospital Banjarmasin. Strengthening the directing and controlling functions is expected to improve nurses' compliance and support patient safety initiatives in hospitals.